A New Evaluation Tool to Obtain Practice-Based Evidence of Worksite Health Promotion Programs - Diane O. Dunet, PhD; Phillip B. Sparling, EdD; James Hersey, PhD; Pamela Williams-Piehota, PhD; Mary D. Hill, BBA; Carl Hanssen, PhD; Frances Lawrenz, PhD; Michele Reyes, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionThe Centers for Disease Control and Prevention developed the Swift Worksite Assessment and Translation (SWAT) evaluation method to identify promising practices in worksite health promotion programs. The new method complements research studies and evaluation studies of evidence-based practices that promote healthy weight in working adults.MethodsWe used nationally recognized program evaluation standards of utility, feasibility, accuracy, and propriety as the foundation for our 5-step method: 1) site identification and selection, 2) site visit, 3) post-visit evaluation of promising practices, 4) evaluation capacity building, and 5) translation and dissemination. An independent, outside evaluation team conducted process and summative evaluations of SWAT to determine its efficacy in providing accurate, useful information and its compliance with evaluation standards.ResultsThe SWAT evaluation approach is feasible in small and medium-sized workplace settings. The independent evaluation team judged SWAT favorably as an evaluation method, noting among its strengths its systematic and detailed procedures and service orientation. Experts in worksite health promotion evaluation concluded that the data obtained by using this evaluation method were sufficient to allow them to make judgments about promising practices.ConclusionSWAT is a useful, business-friendly approach to systematic, yet rapid, evaluation that comports with program evaluation standards. The method provides a new tool to obtain practice-based evidence of worksite health promotion programs that help prevent obesity and, more broadly, may advance public health goals for chronic disease prevention and health promotion.